Arduino Based Automated Shoe Cabinet Door System: Sistem Pintu Lemari Sepatu Otomatis Berbasis Arduino - Moh Fakhri Hibatulloh; Akhmad Ahfas (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Home automation technology is increasingly utilized to support efficiency and convenience in daily activities through the integration of sensors, controllers, and actuators. Specific Background: Automatic door systems have been implemented in various applications, while the adoption of microcontroller-based automation for shoe cabinet access remains limited. Knowledge Gap: Previous studies mainly focused on automatic doors for buildings and access systems, with limited attention given to automated shoe cabinet door mechanisms using ultrasonic sensing and Arduino-based control. Aims: This study aimed to design and develop an Arduino Uno based automation system for opening and closing a shoe cabinet door using ultrasonic sensors as detection components and a servo motor as the driving mechanism. Results: The developed system successfully detected objects at predetermined distances, activated the servo motor to open the cabinet door at approximately 50 cm, and operated the blower through a relay when an object was detected at approximately 10 cm. Testing showed that the ultrasonic sensors, servo motor, and relay operated according to the programmed functions. Novelty: The proposed design applies ultrasonic sensor based automation and Arduino Uno control to a shoe cabinet door system integrated with a blower activation mechanism. Implications: The system demonstrates a practical application of microcontroller-based automation for household furniture, providing a simple approach for automated cabinet access and operation.Highlights: Object detection at approximately 50 cm triggered cabinet access through servo actuation. Distance sensing at approximately 10 cm activated blower operation via relay switching. Integrated hardware components functioned according to programmed control logic during testing. Keywords: Arduino Uno; Ultrasonic Sensor; Home Automation; Servo Motor; Automatic Cabinet Door